Molecular genetic subtypes of non-muscle-invasive bladder cancer: their impact on disease prognosis - Sh. M. Sargsian; S. V. Kotov; A. R. Zaretskiy; A. S. Badlaeva; R. I. Guspanov; S. A. Pulbere; D. V. Litvin (Вестник урологии, 2025)
Introduction. Bladder cancer is one of the most prevalent malignancies, characterized by high rates of recurrence and progression—even in its superficial forms, such as non-muscle-invasive bladder cancer (NMIBC). Recent research has increasingly focused on the molecular and genetic profiles of these tumors, as these factors, together with tumor grade and stage, play a crucial role in determining disease prognosis.Objective. To investigate the impact of molecular genetic subtypes in NMIBC on disease prognosis and assess the feasibility of their evaluation in routine clinical practice.Materials & methods. We conducted a retrospective study that included 162 patients with newly diagnosed primary NMIBC treated at the University Urology Clinic between 2011 and 2021. Subsequently, an IHC study of postoperative material from patients with antibodies to GATA3, CK5/6 and FOXA1 was carried out. Subsequently, patients were monitored, and the percentage of relapses and progressions was assessed depending on the molecular genetic subtype. The median follow-up was 36 months.Results. Based on IHC results, tumors were classified into four subtypes: luminal (96; 59.3%), luminal-like (51; 31.5%), intermediate (5; 3.1%), and basal-squamous-like (10; 6.2%). During follow-up, recurrence and progression rates differed significantly between groups. Luminal tumors exhibited low recurrence (33.3%) and progression rates (2.1%), while luminal-like tumors showed higher recurrence (54.9%) but maintained low progression risk (5.9%). In contrast, intermediate and basal-squamous-like subtypes were associated with aggressive behavior: both demonstrated high recurrence rates (100% and 90.0%, respectively) and elevated progression risk (25.0% and 50.0%, respectively) (p < 0.05).Conclusion. Basal-squamous-like tumors demonstrate the worst prognosis in terms of disease recurrence and progression, necessitating more aggressive treatment, whereas luminal tumors are associated with the most favorable outcomes.